The clinical characteristics and prognosis of COVID‐19 patients with cerebral stroke: A retrospective study of 113 cases from one single‐centre. (21st December 2020) - Yao, Xiaolong; Liu, Shengwen; Wang, Junwen; Zhao, Kai; Long, Xiaobing; He, Xuejun; Kang, Huicong; Yang, Yiping; Ma, Xiaopeng; Yue, Pengjie; Shu, Kai; Tang, Zhouping; et al.
Abstract: To explore the clinical characteristics and prognosis of COVID‐19 patients with cerebral stroke. A total of 2, 474 COVID‐19 patients from February 10th to March 24th, 2020 were admitted and treated in two branches (Optic Valley and Sino‐French New City branch) of the Tongji Hospital. Data on the clinical characteristics, laboratory parameters and prognosis of COVID‐19 patients with or without cerebral stroke were collected and comparatively analysed. Of the 2, 474 COVID‐19 patients, 113 (4.7%) patients had cerebral stroke and 25 (1.0%) patients had new‐onset stroke. Eighty‐eight (77.9%) patients in the previous‐stroke group had cerebral ischaemia, while 25 (22.1%) patients in the new‐onset stroke group had cerebral ischaemia. Most COVID‐19 patients with stroke were elderly with more comorbidities such as hypertension, diabetes and heart diseases than patients without stroke. Laboratory examinations showed hypercoagulation and elevated serum parameters such as IL‐6, cTnI, NT pro‐BNP and BUN. Consciousness disorders, a long disease course and poor prognosis were also more commonly observed in stroke patients. The mortality rate of stroke patients was almost double (12.4% vs. 6.9%) that of patients without stroke. In addition, age, male sex and hypertension were independent predictors for new cerebral stroke in COVID‐19 patients. In conclusion, the high risk of new‐onset stroke must be taken into consideration when treating COVID‐19 patients with an elderly age combined with a history of hypertension. These patients are more vulnerable to multiorgan dysfunction and an overactivated inflammatory response, in turn leading to an unfavourable outcome and higher mortality rate. Abstract : Of the 2, 474 COVID‐19 patients in the Tongji Hospital, 113 (4.7%) patients had cerebral stroke, and 25 (1.0%) patients had new‐onset stroke. In 113 (4.7%) stroke patients, 88 (77.9%) patients in the previous‐stroke, while 25 (22.1%) patients in the new‐onset. Most COVID‐19 patients with stroke were elderly with more comorbidities such as hypertension, diabetes and heart diseases. Laboratory examinations showed hypercoagulation and elevated serum parameters such as IL‐6, cTnI. The mortality rate of stroke patients was almost double that of patients without stroke. In conclusion, COVID‐19 patients with an elderly age combined with a history of hypertension were more likely happening new‐onset stroke. These patients are more vulnerable to multiorgan dysfunction and an overactivated inflammatory response, in turn leading to a higher mortality rate.